FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN PT. ABADI RAYA COMMERCE BALIKPAPAN - Didik Hadiyatno; Imam Ariwibowo; Muhammad Zulkarnain Wijaya; Maswati Maswati; Rio Oktora (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to determine the effect of compensation, work stress, and work discipline partially on job satisfaction of employees of PT. Abadi Raya Commerce Balikpapan. This research was conducted at PT. Abadi Raya Commerce Balikpapan, with 52 respondents, this research method uses quantitative methods. Collecting data by means of observation and distributing questionnaires through google form. The data analysis technique used is multiple linear analysis by performing instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the compensation and work discipline variables had a positive and insignificant effect on job satisfaction, while the work stress variable had a positive and significant effect on job satisfaction.